CHARACTER IMPROVEMENT FOR ELEMENTARY SCHOOL STUDENTS TO PREPARE A QUALIFIED YOUNG GENERATION - Titi Maemunah (Sean Institute, 2023)
An education must be developed dynamically by always following the various developments that occur in society in order to empower the nation's younger generation. An educational institution must be used as a center for the development of intelligence and personality that is able to provide the color and character of a strong generation so that it can be a provision for the next generation of this nation to actively participate in global civilization in a proactive, qualified, independent and reliable manner. Therefore, educational institutions, in addition to providing general and religious knowledge, also make efforts to strengthen personal skills through life skills education for students to survive the life. Based on this, research has been conducted on the development of personal skills to strengthen personal branding at Logarithm Karanganyar Integrated Islamic Elementary School. This research uses a qualitative approach with a case study research type. Data collection techniques with observation, interviews and documentation. Data analysis techniques use inductive methods, deductive data interpretation and comparative methods. The results showed that Logaritma Karanganyar Integrated Islamic Elementary School in developing personal skills is evidenced by the existence of activities that support the development of personal skills (Mandatory prayers in congregation, dhuha prayers, tadarus, scout organization, mukhayam, Study Tour, Industrial Study, out bond, Ramadan pesantren, English club.